Charity, Activism and Social Justice: Revisiting Christian Aid's Role in Public Campaigns for Fair Trade, 1968–1973. (November 2019) - Anderson, Matthew
Abstract: The 1960s was the moment when NGOs established their role within the professional world of international development. There were new networks emerging and new approaches to development – but there were also longer-term trends and challenges that resurfaced about the role of charity, activism and social justice. Previous research has shown how Christian networks were instrumental in establishing local fair trade campaigns. This article investigates the extent to which Christian Aid contributed to fair trade campaigns by providing a moral social force in public debates about social justice, international development and global trade.